Accessing and browsing information and communication - Rice, Ronald E. (MIT Press, 2001)
This book contends that accessing and browsing information and communication are multidimensional and consequential aspects of the information user's entire experience and of general human behavior. Problems in information creation, processing, transmittal, and use often arise from an incomplete conceptualization of the "information seeking" process, where information seeking is viewed as the intentional finding of specific information. The process has traditionally been considered to begin with some kind of search query and end with some kind of obtained information. That, however, may be only the last, most easily observable--and perhaps not even primary--stage of a complex sequence of activities. This book reviews related theory, research, practice, and implications from a wide range of disciplines. It also analyzes converging forms of information, including mass media, online information services, the Internet and World Wide Web, libraries, public spaces, advertisements, and organizational communication. Extensive case studies illustrate the theoretical material